The Impact of Niche Marketing Towards Sales at Pt Sardana Indah Berlian Motor Medan - Jung Sen; Agus Susanto; Elyzabeth Wijaya; Felix Leonardi; Eddy (Jurnal Kolaboratif Sains, 2024)
The company launches the new Strada Triton HD-X. The aim is to know whether there is an impact on how niche marketing of this company can initiate a good outcome towards the sales of the company by doing research. Research will be done in the company and the population taken will be customers of this company that consist of 1,000 people. In this study, the sample that will be taken is 10% of population or 100 people. The questionnaires will contain 12 questions. The Mean of variable X is 4.28 and that of variable Y is 4.37. Most of the validity tests on both variables show high validity. The coefficient of correlation test is 0.74. Determination test results in 54.61% while the hypothesis test results in 7.4. From the data analysis, the writer has finally compiled his research that the data of questionnaires are valid to be processed on this skripsi. Niche marketing can be used in the company to gain profit from smaller market segments. Majority of the customers are males who are 30 years and above and from entrepreneurs’ classes. The correlation of the variables shows a strong positive relationship, in which it explains how strong the impact of niche marketing toward sales and the data can be trusted. Along with the other tests, hypothesis test shows that the null hypothesis must be rejected while the alternative hypothesis must be accepted.